Recycled carbon fibre/Bi2Te3 and Bi2S3 hybrid composite doped with MWCNTs for thermoelectric applications - Jagadish P.; Khalid M.; Amin N.; Hajibeigy M.T.; Li L.P.; Numan A.; Mubarak N.M.; Walvekar R.; Chan A. (Elsevier Ltd, 2023)
Carbon fibers; Carbon nanotubes; Cost effectiveness; Electric conductivity; Electronic equipment; Layered semiconductors; Multiwalled carbon nanotubes (MWCN); Nanotubes; Recycling; Seebeck coefficient; Sulfur compounds; Tellurium compounds; Thermoelectric equipment; Thermoelectricity; Yarn; Bismuth telluride; Hybrid composites; Recycled carbon fibres; Thermoelectric; Thermoelectric application; Thermoelectric composite; Thermoelectric generators; Thermoelectric properties; Bismuth compounds